2002
DOI: 10.1136/sti.78.5.334
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes about sexual disclosure and perceptions of stigma and shame

Abstract: Objectives: To determine the association between stigma and shame about having a sexually transmitted disease and adolescents' past STD related care seeking; between stigma, shame, and perceptions about disclosure of sexual behaviours to a doctor or nurse; and whether the association of stigma, shame, and care seeking was moderated by perceptions about disclosure. Methods: A household sample of 142 sexually active African-American youths, 13-19 years old, was questioned about STD related stigma (alpha = 0.89),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(93 citation statements)
references
References 10 publications
2
89
2
Order By: Relevance
“…We hypothesized that our measure of internalized stigma would be strongly and positively correlated (r=0.5-0.7) with feelings of shame. Shame is one psychological experience an individual may have as a result of internalized stigma, and several studies in the literature have demonstrated these constructs to be separate, but related (Cunningham et al, 2002;Duffy, 2005;Fortenberry et al, 2002). Studies of HIV-positive adults living in the US have also demonstrated that stigma is associated with poor social support and depressive symptoms (Bairan et al, 2007;Carr and Gramling, 2004;Sowell et al, 1997;Vanable et al, 2006).…”
Section: Content and Construct Validity Of Stigma Measurementioning
confidence: 93%
“…We hypothesized that our measure of internalized stigma would be strongly and positively correlated (r=0.5-0.7) with feelings of shame. Shame is one psychological experience an individual may have as a result of internalized stigma, and several studies in the literature have demonstrated these constructs to be separate, but related (Cunningham et al, 2002;Duffy, 2005;Fortenberry et al, 2002). Studies of HIV-positive adults living in the US have also demonstrated that stigma is associated with poor social support and depressive symptoms (Bairan et al, 2007;Carr and Gramling, 2004;Sowell et al, 1997;Vanable et al, 2006).…”
Section: Content and Construct Validity Of Stigma Measurementioning
confidence: 93%
“…[14] STI Stigma was measured using 6 items (e.g., "If you had an STI, people would avoid you", α = .92). [11] STI shame was measured using 5 items (e.g., "If you had an STI, how ashamed would you feel? ", α = .90).…”
Section: Questionnairementioning
confidence: 99%
“…", α = .90). [11] Willingness to disclose sexual histories was measured using four items (e.g., "If you told a doctor/nurse that you had sex with lots of different people, how likely is it that they would think less of you? ", α = .83).…”
Section: Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…While barriers to HIV testing among youth in Iran is poorly understood, decreased uptake of HIV testing among youth has been strongly associated with structural-and individual-level HIV-related stigma in numerous settings (Cunningham, Tschann, Gurvey, Fortenberry, & Ellen, 2002;Shoveller, et al, 2009;Tilson, et al, 2004).…”
Section: Discussionmentioning
confidence: 99%